Pelatihan Perencanaan Keuangan Syariah untuk Keluarga Muslim Kampung Baru Kuala Lumpur Malaysia - Wawan Kusnawan; Mushlih Candrakusuma; Rizki Listyono Putro (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
In a family, Islamic financial planning is a strategic step in realizing economic welfare for the community and the ummah. Islamic financial planning helps a community in a family to design a better life by providing solutions to economic problems through planning, managing and distributing wealth wisely to achieve short-term, medium-term and long-term goals, for the welfare of the hereafter. Muhammadiyah, participates in efforts to realize the welfare of society through the concept of sakinah families that promote Islamic values in building families as a strong foundation for building a prosperous society. As an organization with a global da'wah vision, Muhammadiyah internationalized its movement through the establishment of the Muhammadiyah Special Branch (PCIM) Malaysia in 2007, based in Kampung Baru. Through PCIM Malaysia, Muhammadiyah continues to make breakthroughs in the da'wah movement by establishing various charities to strengthen and develop the community's economic sector, as well as empowering the community through studies, entrepreneurship training and family financial management. With a vision that is in line with the concept of a sakinah family, the proposer together with PCIM Malaysia endeavored to organize community service through Sharia Financial Planning Training activities for Muslim Families of Kampung Baru Kuala Lumpur Malaysia. The solution steps that the proposer will take are (1) providing education to the Muslim community of Kampung Baru to foster high awareness of the importance of financial planning management in a family, (2) building awareness of the urgency of sharia-compliant planning management in carrying out financial management, (3) providing an in-depth understanding of the Fiqh Muamalah review related to the basic concepts of wealth and planning in carrying out wealth management, (4) increasing awareness of a frugal and productive lifestyle based on Islamic values, and (5) assistance and training in accessing Islamic financial products instruments and services to fulfill family financial needs.